RUSSIA’S SILVER AGE IN TODAY’S RUSSIA - Azadovski, Konstantin (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 2001)
The culture of Russia’s Silver Age (1890-1917) has taken its place in the history of the arts of the country after having been forbidden under the Soviet regime. With a relative "thaw" under Khrushchev, the works of Sergei Esenin, Ivan Bunin and some of Marina Tsvetaeva’s works became available. Today, after the fall of the Soviet regime, what used to be forbidden is now widely published often in cheap editions. What used to be elite culture has become mass culture. However, it unclear how the culture of the Silver Age can address the problems of today's extremely politicized Russia. A similar problematic faces the new wave of interest for other cultural trends, which have also garnered the particular interest of Russian society: the culture and literature of Russian emigration and the literature of the Underground.